1990
DOI: 10.1111/j.1467-8624.1990.tb02790.x
|View full text |Cite
|
Sign up to set email alerts
|

Black Grandmothers in Multigenerational Households: Diversity in Family Structure and Parenting Involvement in the Woodlawn Community

Abstract: We report here the frequency of black grandmothers' coresidence in households with first-grade children, their patterns of involvement in parenting, and the degree to which family structure and employment affected the grandmothers' parenting involvement in a 1966/1967 community-defined population. Coresidence between grandmothers and their target first-grade grandchildren was found in 10% of the households. The 130 grandmothers' parenting involvement was substantial, second only to mother involvement, and was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…Approximately two-thirds of both samples endorsed shared caregiving, illustrating that this is a common pattern of parenting among African American adolescent mothers and grandmothers (Pearson, Hunger, Cook, Ialongo, & Kellam, 1997;Pearson, Hunger, Ensminger, & Kellam, 1990). In the present study, mothers were more likely than grandmothers to report full caregiving responsibilities, perhaps reflecting their desire to be independent parents.…”
Section: Discussionmentioning
confidence: 93%
“…Approximately two-thirds of both samples endorsed shared caregiving, illustrating that this is a common pattern of parenting among African American adolescent mothers and grandmothers (Pearson, Hunger, Cook, Ialongo, & Kellam, 1997;Pearson, Hunger, Ensminger, & Kellam, 1990). In the present study, mothers were more likely than grandmothers to report full caregiving responsibilities, perhaps reflecting their desire to be independent parents.…”
Section: Discussionmentioning
confidence: 93%
“…Whereas African American teen mothers were more likely than European American teen mothers to live with grandparental figures, European Americans were more likely than African Americans to be married or living with a partner. Past research~e.g., Apfel & Seitz, 1991;Burton, 1990;Hogan, Hao, & Parish, 1990;Pearson, Hunter, Ensminger, & Kellam, 1990! has suggested that intergenerational support is of particular importance for young African American mothers.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, however, researchers from various theoretical perspectives are contributing to a growing literature on children's and adolescents' social relationships with nonmaternal adults (Cochran, Larner, Riley, Gunnarsson, & Henderson, 1990;Cohen, 1993;King, 1994;Pearson, Hunter, Ensminger, & Kellam, 1990;King, 1994;Taylor, 1996). Concern with children's relationships with fathers and other nonmaternal adults is especially relevant for children residing in unmarried-mother households.…”
Section: Introductionmentioning
confidence: 97%